Outbreak of Ascotis selenaria (Lepidoptera: Geometridae) on Neem and Bakain in the State of Haryana, India - Chander, Jagdish; Singh, Sudhir (Indian Forester, 2017)
Outbreak of Ascotis selenaria (Lepidoptera: Geometridae) in neem (Azadirachta indica) and bakain (Melia azedarach) road side plantations and naturally growing trees in forest and agricultural lands in Haryana and Punjab has been reported. Insect pests of neem, a brief biology of A. selenaria and its natural enemies, especially braconid which was found en mass parasitizing the loopers have been discussed. Various control measures have also been suggested. Observations on effect of defoliation on quality and germination of bakain seed were also studied.